Empagliflozin after acute myocardial infarction - Butler, Javed; Jones, W. Schuyler; Udell, Jacob A.; Anker, Stefan D.; Petrie, Mark C.; Harrington, Josephine; Mattheus, Michaela; Zwiener, Isabella; Amir, Offer; Bahit, M. Cecilia; Bauersachs, Johann; Bayes-Genis, Antoni; et al. (The New England journal of medicine, 2024)
Among patients hospitalized for acute myocardial infarction and at risk for heart failure, empagliflozin did not lead to a significantly lower risk of a first heart-failure hospitalization or death from any cause than placebo.
Online veröffentlicht: 6. April 2024
Gesehen am 27.01.2025